Modeling structural change in spatial system dynamics: A Daisyworld example. (March 2015) - Neuwirth, C.; Peck, A.; Simonović, S.P.
Abstract: System dynamics (SD) is an effective approach for helping reveal the temporal behavior of complex systems. Although there have been recent developments in expanding SD to include systems' spatial dependencies, most applications have been restricted to the simulation of diffusion processes; this is especially true for models on structural change (e.g. LULC modeling). To address this shortcoming, a Python program is proposed to tightly couple SD software to a Geographic Information System (GIS). The approach provides the required capacities for handling bidirectional and synchronized interactions of operations between SD and GIS. In order to illustrate the concept and the techniques proposed for simulating structural changes, a fictitious environment called Daisyworld has been recreated in a spatial system dynamics (SSD) environment. The comparison of spatial and non-spatial simulations emphasizes the importance of considering spatio-temporal feedbacks. Finally, practical applications of structural change models in agriculture and disaster management are proposed. Highlights: Simulation of evolving spatial structures has been widely neglected so far in SSD. The simulation requires bidirectional and synchronous interaction between System Dynamics and GIS applications. Daisyworld is used to illustrate the tight coupling approach. Results highlight the importance of considering spatio-temporal feedbacks.